Development and psychometric testing of the dyadic communication observational coding scheme in DEmentia care (DCODE): family dyadic communication in dementia - Kim, Sohyun; Liu, Wen; Daack-Hirsch, Sandra; Williams, Kristine N. (Aging & mental health, 2023)
Understanding family dyadic communication in dementia is essential to promote the well-being of family caregivers and persons living with dementia. The Dyadic Communication Observational coding scheme in DEmentia care (DCODE) was developed and tested to assess family dyadic communication in dementia. The DCODE was developed from a review of literature, expert review, and pretesting. A secondary analysis of the 75 in-home care video observations from 19 family caregiver-care recipient dyads was conducted to test psychometric properties. The DCODE consists of 43 caregiver items and 41 care recipient items. We observed internal consistency, intra-rater reliability, and inter-rater reliability as adequate. Content validity and convergent validity were moderate. Predictive validity was moderate in predicting caregiver burden. The overall psychometric properties demonstrated a moderate quality of the DCODE. Findings provided the preliminary psychometric evidence of the DCODE as a promising instrument to assess family dyadic communication in dementia. Future testing for concurrent, divergent, and structural validity of the DCODE is needed.